Information literacy and information skills instruction : applying research to practice in the 21st century school library - Thomas, Nancy Pickering (Libraries Unlimited, 2011)
"This book provides a comprehensive review of the current research relating to the teaching of library and information literacy skills as part of effective school library media center programming"--